Friends in low places: How peer advice and expected leadership feedback affect staff auditors’ willingness to speak up - Griffith, Emily E.; Kadous, Kathryn; Proell, Chad A. (Accounting, Organizations and Society, 2020)
Junior auditors collect the bulk of audit evidence, yet they do not always speak up to communicate potentially important audit issues. Such inappropriate “voice” decisions can endanger audit quality. We examine whether and how staff auditors influence each other in making voice decisions. First, a survey provides descriptive evidence that staff auditors consult their peers for advice on whether to speak up. Next, two experiments provide evidence that voice advice among peers at the staff level can be problematic. We find that staff auditors consistently underestimate the importance of raising issues compared to their supervisors, and they rely on social cues that are not diagnostic of issue importance in giving voice advice to peers. Finally, we predict and find that staff auditors tend to follow peer advice when it confirms their initial stance, and that an expectation of high (versus low) quality supervisor feedback increases their willingness to speak up. Most importantly, we find that contradictory peer advice only influences staff auditors’ willingness to speak up when leadership feedback is not expected to be of high quality. Together these results indicate that staff auditors seek out and follow voice advice from their peers, but appropriate leadership feedback practices can mitigate the negative impact of peer advice on upward communication.